About the global effect and the critical role of retinal eccentricity: Implications for eye movements in reading - Françoise Vitu (Bern Open Publishing, 2008)
In the present paper, I review evidence for the universality of the global effect, i.e. the general tendency to move the eyes towards the centre of gravity of the peripheral configu-ration, and show that the effect is strongly constrained by the retinal location of the stimuli. First, stimuli that are displayed in a central foveal region of a 1-1.5° radius fail to deviate the eyes in a centre-of-gravity manner; this is referred to as the foveal dead zone. Second, the stimuli that are too eccentric relative to the saccade target and/or the main stimulation site are filtered out. These limitations reflect physiological constraints and the dynamics of the patterns of activity in a visual saliency map. They form the basis for a low-level centre-of-gravity type account of eye guidance in natural perceptual tasks such as reading.